2015
DOI: 10.1037/ebs0000055
|View full text |Cite
|
Sign up to set email alerts
|

Relationship satisfaction as a function of mate value.

Abstract: It has been proposed that mate value influences both the mate selection process and the quality of a romantic relationship once it has been formed. The aim of this study was to test the relations among perceived own and partner's mate value and relationship satisfaction. As a relationship is a dynamic process, in which assessments made by 1 member of the pair are not independent of the assessments made by the other member, we used an actorpartner interdependence model to test how one's assessments of own and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…Thus, this research introduces the possibility that LLs may be a predictor of relational satisfaction, adding it to an emerging list that includes (a) appreciation of one’s partner’s strengths (Kashdan et al, 2018), (b) attachment security (Diamond, Brimhall, & Elliott, 2018; Eğeci & Gençöz, 2006), (c) communication (Eğeci & Gençöz, 2006; Gordon & Chen, 2016; Mark & Jozkowski, 2013; Yoo et al, 2014), (d) social support (Elegbede & Ogunleye, 2018), (e) emotional intelligence (Sened et al, 2017; Smith et al, 2008), (f) Adlerian birth order (Crain, 2017), (g) Bowenian differentiation of self (Norona & Welsh, 2016), (h) Big Five personality traits (Furler et al, 2014; Hudson & Fraley, 2014; Weidmann, Ledermann, & Grob, 2017), (i) political attitudes and personal values (Leikas et al, 2018), (j) work–life balance (Yucel, 2018), (k) sexual satisfaction (Fallis, Rehman, Woody, & Purdon, 2016; Mark & Jozkowski, 2013; Yoo et al, 2014), (l) perception of mate value (Hromatko, Bajoghli, Rebernjak, Joshaghani, & Tadinac, 2015), and (m) consistency between ideal standards and perceived attributes in one’s partner (Buyukcan-Tetik, Campbell, Finkenauer, Karremans, & Kappen, 2017). Conversely, detractors to relationship satisfaction include (a) viewing one’s partner’s personality strengths as having significant costs (Kashdan et al, 2018), (b) incongruence of motives for being involved in the relationship (Hagemeyer et al, 2013), (c) hypermasculinity (Karakis & Levant, 2012; Lentz, 2017), and (d) inconsistent interpersonal behavior (Sadikaj et al, 2015), dominant behavior (Sadikaj, Moskowitz, & Zuroff, 2017), shyness (Luster et al, 2013), and depression (Li & Johnson, 2018) in one’s partner.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this research introduces the possibility that LLs may be a predictor of relational satisfaction, adding it to an emerging list that includes (a) appreciation of one’s partner’s strengths (Kashdan et al, 2018), (b) attachment security (Diamond, Brimhall, & Elliott, 2018; Eğeci & Gençöz, 2006), (c) communication (Eğeci & Gençöz, 2006; Gordon & Chen, 2016; Mark & Jozkowski, 2013; Yoo et al, 2014), (d) social support (Elegbede & Ogunleye, 2018), (e) emotional intelligence (Sened et al, 2017; Smith et al, 2008), (f) Adlerian birth order (Crain, 2017), (g) Bowenian differentiation of self (Norona & Welsh, 2016), (h) Big Five personality traits (Furler et al, 2014; Hudson & Fraley, 2014; Weidmann, Ledermann, & Grob, 2017), (i) political attitudes and personal values (Leikas et al, 2018), (j) work–life balance (Yucel, 2018), (k) sexual satisfaction (Fallis, Rehman, Woody, & Purdon, 2016; Mark & Jozkowski, 2013; Yoo et al, 2014), (l) perception of mate value (Hromatko, Bajoghli, Rebernjak, Joshaghani, & Tadinac, 2015), and (m) consistency between ideal standards and perceived attributes in one’s partner (Buyukcan-Tetik, Campbell, Finkenauer, Karremans, & Kappen, 2017). Conversely, detractors to relationship satisfaction include (a) viewing one’s partner’s personality strengths as having significant costs (Kashdan et al, 2018), (b) incongruence of motives for being involved in the relationship (Hagemeyer et al, 2013), (c) hypermasculinity (Karakis & Levant, 2012; Lentz, 2017), and (d) inconsistent interpersonal behavior (Sadikaj et al, 2015), dominant behavior (Sadikaj, Moskowitz, & Zuroff, 2017), shyness (Luster et al, 2013), and depression (Li & Johnson, 2018) in one’s partner.…”
Section: Discussionmentioning
confidence: 99%
“…3. Body dissatisfaction typically arises through a combination of genetic risk with stress created through perceived mate value or the self-perception that one is able to attract desirable mates (Hromatko, Bajoghli, Rebernjak, Joshaghani, & Tadinac, 2015).…”
Section: A Theoretical Structure For Limited Media Effectsmentioning
confidence: 99%
“…This finding is somewhat consistent with the findings of Nowak and Danel [ 61 ] who reported that relationship satisfaction is positively associated with women’s perception of their partners’ mate value. Research results show that mate value discrepancy affects relationship satisfaction, communication commitment, and mate retention behaviors [ 26 , 62 ]. For example, research by Nowak and Danel [ 61 ] has shown that women’s evaluations of their partners’ mate value play a more important role in relationship satisfaction than their own mate value.…”
Section: Discussionmentioning
confidence: 99%
“…One’s partner’s mate value is the strongest predictor of relationship satisfaction in general [ 26 ]. Both men and women who perceived their partners to have a higher mate value reported a higher level of satisfaction with their relationship [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation